FeNO as a biomarker for airway inflammation due to exposure to air pollutants among school children nearby industrial areas in Terengganu - Kamaruddin, Anis Syafiqah; Jalaludin, Juliana; Hamedon, Titi Rahmawati; Hisamuddin, Nur Hazirah (Universiti Putra Malaysia Press, 2019)
Exposure to industrial air pollutants is a public health concern particularly in children due to their immaturity of respiratory systems. The distance between their school and home from the industrial area will elevate the risk of airway inflammation among children. This study aims to determine the exposure of Industrial Air Pollutants (PM10, PM2.5, NO2, SO2, and VOCs) and its association with airway inflammation (FeNO) among primary school children in industrial and non- industrial areas in Kemaman, Terengganu. A cross-sectional comparative study was conducted among Malay primary school children in Kemaman, Terengganu. A validated questionnaire was randomly distributed to children to get the background information, respiratory symptoms and exposure history of the children. The assessment of indoor air quality was carried out in each primary school and home using indoor air monitoring equipment. Fractional exhaled nitric oxide (FeNO) was measured using an NIOX MINO device. The results showed a significant difference between concentrations of PM10, PM2.5, NO2, SO2, and VOCs in different classrooms from selected schools and homes of exposed and comparative groups, P<0.05. Statistical analysis revealed that the FeNO level was significantly higher among the exposed group compared to the comparative group (Z= -9.442, p= 0.001). The research suggests that the exposure to industrial air pollutants will increase the risk of getting respiratory inflammation among primary school children living near industrial areas.